What is the meaning of “Diaspora” in the times of globalization? The controversial relationship between Empire, Lusophony and “portugalidade” - Sousa, Vítor Manuel Fernandes Oliveira (2014)
Publicado em "Colonialisms, post-colonialisms and lusophonies: proceedings of the 4th International Congress in Cultural Studies". ISBN 978-989-98219-2-7